Hard carbon material and preparation method thereof
Through two-stage oxidation treatment and crosslinking technology, the problem of asphalt materials generating orderly graphite structures at high temperatures is solved, forming amorphous carbon material with high capacity and high magnification performance. It is suitable for the negative electrode of sodium ion battery, simplifying the process and Reduced costs.
Patent Information
- Application Number
- CN202411376432.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing hard carbon anode materials based on asphalt are prone to generate high orderly graphite structures during high-temperature pyrolysis, which limits the storage capacity of sodium ions, and the preparation process is complex and uneconomical.
The asphalt is treated with two-stage oxidation, first pre-oxidation is performed under an oxidative atmosphere, and oxygen-containing functional groups are introduced, and then cross-linked with polymer and small molecule cross-linking agent to form a closed-cell structure, avoiding the introduction of strong acids or oxidants, and simplifying the process .
The cross-linking degree and softening point of asphaltene are improved, the molten state rearrangement is suppressed, and amorphous carbon materials with high capacity and high rate performance are formed. They are suitable for the negative electrode of sodium ion battery, simplifying the preparation process and reducing costs.
Smart Images

Figure CN119191268A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of materials, and in particular to a hard carbon material and a preparation method thereof. Background Art
[0002] As the global demand for sustainable development becomes increasingly urgent, the development and utilization of new energy technologies has become crucial. As the core of energy storage solutions, secondary battery technology plays a vital role in promoting efficient conversion and stable storage of energy. The development of this technology has an important role in integrating renewable energy resources such as wind energy, solar energy and geothermal energy into the power grid. It can not only optimize the energy structure, but also significantly improve the efficiency of renewable energy use, laying a solid foundation for building a low-carbon society. In recent years, with the growing demand for clean energy, sodium-ion batteries have become another research hotspot besides lithium batteries due to their abundant resources and low cost. The development of sodium batteries is expected to solve the scarcity, distribution limitations and high cost of lithium resources, and has attracted the attention of researchers at home and abroad. Sodium ions have similar structures to lithium ions and have similar energy storage processes. Based on the research and development experience of lithium battery positive electrode materials, the research on positive electrode materials has made certain progress and met the needs of initial applications. However, the radius of sodium ions is larger than that of lithium ions, which means that the graphite anode commonly used in lithium batteries cannot be directly used in sodium batteries, limiting its further development.
[0003] Among the reported negative electrode materials for sodium-ion batteries, amorphous carbon materials are considered to be highly promising candidate materials due to their low sodium storage potential, high capacity and good cycle stability. Asphalt, as a byproduct of coal chemical industry, has the advantages of low cost, high carbonization rate and easy mass production as a raw material for amorphous carbon materials, showing great market potential. However, the carbon material prepared by direct calcination of asphalt has a too high structural order and insufficient porosity, which limits the sodium storage capacity of the platform area and leads to low battery energy density.
[0004] CN118651846A discloses a hard carbon negative electrode material and a preparation method thereof. The hard carbon negative electrode material is prepared by using a carbonization precursor containing a polysulfide compound and subjecting it to two carbonization treatments. The polysulfide compound is prepared by a reverse vulcanization reaction of elemental sulfur and a polyene compound, and the elemental sulfur and the polyene compound achieve self-crosslinking at the molecular level.
[0005] CN118553898A discloses a hard carbon composite negative electrode material, wherein the core is a sodium-phosphorus co-doped hard carbon material and the shell is a carbon layer. The preparation method comprises the following steps: (1) mixing an acid-based resin, an organic acid, a sodium source, a crosslinking agent and an organic solvent, and reacting to obtain a hard carbon precursor material; (2) pre-carbonizing the hard carbon precursor material, then doping it with phosphorus, and then coating it with carbon to obtain the hard carbon composite negative electrode material.
[0006] CN118553897A discloses a hard carbon composite material and a preparation method thereof, the preparation method comprising the following steps: (a) mixing a metal conductive agent, a sodium ion solid electrolyte, a sodium supplement, a binder and an organic solvent to obtain a coating liquid; b) mixing a resin precursor and a crosslinking agent, curing and crosslinking to obtain an intermediate, and then mixing the intermediate with asphalt, and carbonizing the intermediate to obtain an asphalt-based hard carbon material in a secondary particle morphology; (c) mixing the asphalt-based hard carbon material and the coating liquid, and sintering the hard carbon composite material. The crosslinking agent includes any one of hexanediol diacrylate, triallyl isocyanurate, trimethylolpropane triacrylate or pentaerythritol triacrylate, or a combination of at least two thereof.
[0007] CN118373409A discloses a sodium ion battery hard carbon negative electrode material based on phenolic resin, wherein a linear phenolic resin and an epoxy resin are mixed evenly to obtain a composite resin, a curing agent is added and mixed evenly, and then cured, and then crushed, refined, and sieved to obtain a cured resin powder; resin carbonization: the cured resin powder is sintered at low temperature under an inert gas protection state, carbonized at high temperature, cooled, and discharged to obtain a sodium ion battery hard carbon negative electrode material. The curing agent includes urotropine and maleic anhydride; wherein the mass ratio of urotropine to maleic anhydride is 15:(0.8-1.2)
[0008] CN118289738A discloses a biomass hard carbon material and a method for preparing the biomass hard carbon material by pre-crosslinking modification, comprising the following steps: mixing the biomass raw material with a polycarboxylic acid and placing it in a sealed reactor for a solid-gas two-phase crosslinking reaction to obtain a pre-crosslinked material; and carbonizing the pre-crosslinked material at high temperature to obtain the biomass hard carbon material.
[0009] CN118198309A discloses a method for preparing an asphalt-based hard carbon composite material, comprising the following steps: S1, mixing asphalt, an organic solvent, a heteroatom compound, and a scandium salt, freeze-drying, and obtaining a hard carbon precursor material; S2, heating a peroxide cross-linking compound to a preset temperature to obtain a cross-linking gas; cross-linking and curing the cross-linking gas and the hard carbon precursor material to obtain an intermediate material; S3, mixing a fast ion conductor, a conductive agent, and the intermediate material, drying, and carbonizing to obtain the asphalt-based hard carbon composite material.
[0010] CN118026145A discloses a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material, the preparation method of which comprises the following steps: (1) physically mixing amino-containing biomass A, hydroxyl-containing biomass B and a cross-linking agent to obtain a uniform mixture; (2) transferring the mixture to a homogeneous reactor for cross-linking reaction at a temperature of 60 to 70 °C;
[0011] 150°C, the cross-linking reaction time is 1 to 10 hours, and a structurally stable cross-linked mixture C is obtained; (3) Under an inert atmosphere, the cross-linked mixture C is subjected to low-temperature pretreatment, the temperature is increased to 200 to 600°C at a heating rate of 1 to 5°C / min, the temperature is kept constant for 1 to 6 hours, and the intermediate product is cooled to room temperature to obtain; (4) Under an inert atmosphere, the intermediate product is subjected to high-temperature carbonization, the temperature is increased to 900 to 1500°C at a rate of 1 to 10°C / min and the temperature is kept constant for 0.5 to 8 hours, and after cooling to room temperature, a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material is obtained.
[0012] CN116404138A discloses a biomass hard carbon negative electrode composite material and a preparation method thereof, comprising the following steps: S1. oxidizing hydrocarbons to obtain oxides, mixing the oxides and polyhydroxy organic acids, dehydrating and carbonizing to obtain a hard carbon intermediate material; S2. dissolving a metal compound and a phosphate-type dispersant in an organic solvent to prepare a metal solution, atomizing and depositing the metal solution on the surface of the hard carbon intermediate material by a gas atomization method to obtain a metal-deposited hard carbon precursor material; S3. transferring the metal-deposited hard carbon precursor material to a tubular furnace and introducing a carbon source mixed gas for carbonization to obtain a biomass hard carbon negative electrode composite material.
[0013] The above patents all use different technical means to cross-link the carbon source in order to obtain a hard carbon negative electrode material with better electrochemical performance. However, when asphalt-based carbon materials are used as raw materials, due to the low softening point of asphalt, the asphalt is rearranged in the molten state during high-temperature pyrolysis, and the conjugated structure in the asphaltene molecules is accumulated under the action of van der Waals forces, which makes it easy to generate a highly ordered graphite structure, which is not conducive to the storage of sodium ions. The present invention proposes a two-stage oxidation of asphalt, and successively uses polymers and small molecules rich in acid anhydride or carboxylic acid structures as cross-linking agents, which can react with asphalt molecules during the pre-carbonization process to increase the molecular weight and cross-linking degree of asphaltene, increase the softening point, and inhibit the molten rearrangement process. More importantly, during the pyrolysis process, these oxygen-containing functional groups can be cracked to release a large number of gaseous small molecules, realize in-situ etching of the carbon layer, and help form closed pores. Unlike the currently commonly used strategy for increasing the cross-linking degree of asphalt, the method of the present invention does not require the introduction of strong acids or strong oxidants, as well as inorganic salts that are difficult to remove, avoiding the complex steps of subsequent impurity removal. More importantly, while simplifying the steps, the carbonization rate can also be increased, thereby improving the economy and sustainability of the preparation process. Summary of the invention
[0014] In order to solve the problem that the electrochemical performance of the existing asphalt-based hard carbon negative electrode materials cannot meet the needs of industrial batteries, the present invention provides a sodium ion battery negative electrode material and a preparation method and application thereof, using coal tar asphalt, petroleum asphalt and intermediate phase asphalt, which are abundant and low-priced by-products of coal chemical industry, as raw materials, pre-treated in an oxidizing atmosphere, introducing oxygen-containing functional groups, improving the softening point and cross-linking degree, and inhibiting the rearrangement of asphaltene in the molten state.
[0015] In order to solve the above technical problems, the present invention provides a method for preparing a hard carbon material, comprising the following steps:
[0016] (S1) crushing the asphalt and performing heat treatment in an oxidizing atmosphere to obtain a pre-oxidized precursor;
[0017] (S2) the pre-oxidized precursor is mixed evenly with the cross-linking agent I, and a cross-linking is performed once under an inert atmosphere and heating conditions to obtain a cross-linked precursor I; the cross-linking agent I is a polymer having a carboxyl group in the side chain;
[0018] (S3) The cross-linking precursor I and the cross-linking agent II are mixed evenly, and secondary cross-linking is performed under an inert atmosphere and heating conditions to obtain a cross-linking precursor II; the cross-linking agent II is a small molecule aromatic compound containing multiple anhydride and / or carboxyl groups.
[0019] (S4) The cross-linked precursor II is calcined, cooled and ground under an inert atmosphere to obtain an amorphous sodium ion battery negative electrode material.
[0020] Furthermore, the sodium ion battery negative electrode material obtained by the present invention has an irregular morphology, a particle size of 1-20 μm, and a particle size of 1-20 μm. 002 The value is between 0.36-0.40nm.
[0021] Furthermore, in step (S1), the asphalt-like substance includes one or more mixtures of coal tar asphalt, petroleum asphalt, natural asphalt and mesophase asphalt; crushed to a particle size of less than 5 mm. The crushing method is not particularly limited, including but not limited to air flow crushing, high-speed crushing, and grinding. The oxidizing atmosphere includes at least 20% volume of oxygen, such as oxygen, air, a mixture of nitrogen and oxygen, and a mixture of carbon dioxide and oxygen. The oxidizing atmosphere may also contain an ozone atmosphere. The heat treatment is to slowly heat up to 250-300°C and keep warm for 5-10h; preferably, the slow heating rate is 1-3°C / min.
[0022] In the pre-oxidation step of step (S1), slow heating and short-term heat preservation are conducive to fully contacting the asphaltene with the molecules in the oxidizing atmosphere, promoting the reaction between the two. The full oxidation of asphaltene can reduce the hydrogen atoms in the asphaltene as much as possible, inhibit its subsequent molten state rearrangement, and is conducive to forming a uniform cross-linked structure. In addition, the full pre-oxidation of asphalt can form more oxygen-containing functional groups such as hydroxyl, carboxyl, etc., which can react with the carboxylic acid / anhydride in the cross-linking agent added later to form an ester group, and promote the cross-linking and pyrolysis of asphaltene molecules into short-range mutually cross-linked graphite domains during the subsequent calcination, and the graphite domains can be bent to form a closed-cell structure that helps to fill sodium clusters. If the heating rate is too fast during the pre-oxidation process, the asphalt surface is quickly cross-linked, which will lead to insufficient flow of asphaltene, so that the local area of the asphalt is directly polycondensed to form highly ordered mesophase carbon microspheres, and long-range ordered and tightly stacked graphene layers are formed in the subsequent high-temperature carbonization process, which is not conducive to the insertion and filling process of sodium ions, resulting in a decrease in the capacity of the platform area.
[0023] Further, in step (S2), the crosslinking agent I is selected from at least one of polyacrylic acid, polymethacrylic acid, and alginic acid; preferably, the number average molecular weight of the crosslinking agent I is 4000-20000 g / mol; more preferably, the amount of the crosslinking agent I is 5-10wt% of the pre-oxidized precursor. In a preferred embodiment, the number average molecular weight of polyacrylic acid and polymethacrylic acid is 4000-6000 g / mol, and the molecular weight of alginic acid is 10000-20000 g / mol.
[0024] Furthermore, in step (S2), the process conditions for the primary cross-linking are heat treatment at 300-600°C for 5-10h.
[0025] Furthermore, in step (S3), the crosslinking agent II is selected from at least one of terephthalic acid, phthalic acid, isophthalic acid, gallic acid, perylenetetracarboxylic anhydride, trimesic acid, and pyromellitic anhydride. The amount of the crosslinking agent II is 3-6wt% of the crosslinking precursor I.
[0026] Furthermore, in step (S3), the process conditions for secondary cross-linking are firstly heating to 250-400°C at a heating rate of 5-10°C / min, keeping warm for 1-2h, and then slowly heating to 400-600°C at a heating rate of 5-10°C / min and keeping warm for 3-5h.
[0027] The present invention sequentially uses polymer crosslinking agent I and small molecule crosslinking agent II to crosslink asphalt. During the crosslinking process, anhydride or carboxylic acid can react with the hydroxyl group in asphalt to form an ester group, which helps the asphalt to pyrolyze to form amorphous carbon. Wherein the polymer crosslinking agent I can form a three-dimensional network structure in combination with asphalt, forming volatile small molecules during high-temperature pyrolysis, and the oxygen-containing functional groups carried by such substances themselves can be cracked into gaseous small molecules containing carbon dioxide at high temperatures, which can react with the carbon layer inside the asphalt-based carbon material to form closed pores, defects and heteroatom groups, increase the interlayer spacing of the graphite domain area, and facilitate the adsorption, intercalation and pore filling of sodium ions on the surface of the carbon negative electrode, thereby forming closed micropores and defects in the crosslinked polymerized asphalt carbon, so that the sodium storage performance of the obtained negative electrode material is greatly improved, but it also leads to a low first effect and poor rate performance. Small molecule crosslinking agent II contains an aromatic structure, and the introduction of such substances can help improve conductivity, reduce surface defects, and help improve the rate. This strategy takes into account both high capacity and high rate, and proposes a carbon material with low cost, simple preparation process, high carbon yield, and easy large-scale production, and applies it as a negative electrode material in sodium batteries.
[0028] Furthermore, in step (S2) and step (S3), the method for uniform mixing includes but is not limited to ball milling, mechanical crushing, and high-speed mixer, preferably ball milling. The process parameters of ball milling are well known in the art. In a specific embodiment of the present invention, the uniform mixing is ball milling, and the ball milling process parameters are directly placing the anhydride or carboxylic acid and the asphalt in a ball milling tank, and the ball milling process parameters are a ball-to-material ratio of 10-20:1, which is translated as 600-1000rpm and a ball milling time of 5-8h.
[0029] Furthermore, in steps (S2), (S3) and (S4), the inert atmosphere is at least one of argon and nitrogen.
[0030] Furthermore, in step (S4), the hydrocarbon is at least one of methane, ethane, propane, butane, ethylene, acetylene, and toluene; and the calcination is performed by heating the temperature to 1000-1500° C. at a heating rate of 5-10° C. / min and calcining for 3-8 hours.
[0031] The sodium ion battery negative electrode material prepared by the present invention is in the form of irregular blocks, wherein a graphite layer is formed on the surface of the carbon material after reacting with the crosslinking agent II, thereby improving the first efficiency and cycle stability. The present invention uses asphalt-like substances as raw materials, which are cheap and readily available. After pre-oxidation, the raw materials are mixed with anhydrides or carboxylic acids, and then pre-carbonized to make the asphalt isotropically cross-linked, thereby inhibiting the formation of mesophase carbon microspheres by asphaltene. By utilizing the difference between the pyrolysis behavior of the oxygen-containing functional groups in the crosslinking agent and the asphaltene, small gas molecules are formed to help the carbon material form closed pores in situ, thereby obtaining a sodium battery carbon negative electrode material with high capacity and high rate performance.
[0032] The present invention also provides an ion battery hard carbon negative electrode material, which is prepared by the above preparation method.
[0033] The present invention also provides a sodium battery carbon negative electrode plate, comprising: a current collector, a binder, a conductive agent and the sodium ion battery negative electrode material prepared by the above preparation method.
[0034] The present invention also provides a sodium ion secondary battery, the negative electrode of which comprises the sodium ion battery negative electrode material prepared by the above preparation method.
[0035] The sodium ion battery negative electrode material based on coal chemical byproducts provided by the present invention and its preparation method and application use a wide range of sources and low-priced asphalt-based substances as raw materials, and sequentially use a polymer crosslinker I and a small molecule crosslinker II for two-step crosslinking, taking into account high capacity and high rate performance, and developing a low-cost, simple preparation process, controllable structural disorder, and high residual carbon rate amorphous carbon material, and used as a negative electrode material for sodium ion secondary batteries. The sodium ion secondary battery made of the negative electrode material of the present invention exhibits a higher operating voltage and good rate performance, which is not only suitable for the energy supply of mobile devices and electric vehicles, but also can meet the energy storage needs in the fields of renewable energy power generation and energy storage, smart grid peak regulation, distributed power stations, backup power supplies, and communication base stations. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is the charge and discharge curve of the carbon negative electrode prepared by coal tar pitch (XLC), comparative example 1 (OXLC) and example 1 (POXLC).
[0037] Figure 2 High-resolution transmission electron microscopy images of Example 1 and Comparative Example 1.
[0038] Figure 3 It is the XRD diagram of the carbon negative electrode prepared in Comparative Example 1 (OXLC) and Example 1 (POXLC).
[0039] Figure 4 It is a constant current charge and discharge curve diagram of Example 1 (POXLC) at different current densities. DETAILED DESCRIPTION
[0040] The asphalt-based sodium ion battery amorphous carbon negative electrode material of the present invention is further described below in conjunction with specific embodiments and the accompanying drawings of the specification, but it should be understood that the protection scope of the present invention is not limited to the following embodiments.
[0041] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0042] Example 1
[0043] (S1) Weighing 100 parts by mass of blocky coal tar pitch, crushing it, and then sieving it (200 mesh), placing the resulting pitch powder on aluminum foil, heating it to 300° C. at a rate of 3° C. / min in air and keeping it at that temperature for 10 h to obtain a pre-oxidation precursor;
[0044] (S2) The pre-oxidized precursor and polyacrylic acid (number average molecular weight of about 4000 g / mol) were ball-milled at a mass ratio of 100:4, a ball-to-material ratio of 10:1, a rotation speed of 600 r, and a ball-milling time of 5 h. The mixture obtained after ball milling was sheeted, and the temperature was increased to 600° C. at a heating rate of 10° C. / min under an argon atmosphere, and the temperature was kept at this temperature for 5 h. After cooling, a cross-linked precursor I was obtained.
[0045] (S3) cross-linking precursor I and perylenetetracarboxylic dianhydride are ball-milled in a mass ratio of 100:10, with a ball-to-material ratio of 10:1, a rotation speed of 600r, and a ball-milling time of 5h. After ball-milling, the mixture is sheeted. After the sheet is sheeted, it is heated to 300°C at a heating rate of 5°C / min in an argon atmosphere, kept warm for 2h, and then heated to 400°C at a heating rate of 5°C / min, kept warm for 4h, and cooled to obtain cross-linking precursor II;
[0046] (S4) placing the cross-linked precursor II in a high temperature tube furnace, heating it to 1300° C. at a rate of 5° C. / min in an argon atmosphere, keeping the temperature for 4 h, and cooling it to room temperature to obtain an amorphous carbon negative electrode material.
[0047] (S5) The obtained amorphous carbon negative electrode material, conductive additive SP, and binder CMC / SBR are mixed in a weight ratio of 94:2:4, dissolved in solvent water, and stirred to obtain a uniform slurry, and then the slurry is evenly coated on the carbon-coated aluminum foil with a 50μm scraper, dried, and sliced to obtain a negative electrode sheet.
[0048] Comparative Example 1
[0049] The other conditions are the same as those in Example 1, steps (S2) and (S3) are omitted, and the pre-oxidized precursor obtained in step (S1) is directly subjected to high-temperature calcination in an argon atmosphere in step (S4).
[0050] Comparative Example 2
[0051] The other conditions are the same as those in Example 1, except that step (S2) is eliminated, and the pre-oxidized precursor obtained in step (S1) is directly subjected to step (S3), i.e., the pre-oxidized precursor and perylenetetracarboxylic dianhydride are ball-milled and mixed in a mass ratio of 100:10, and the subsequent steps are the same as in Example 1.
[0052] Comparative Example 3
[0053] The other conditions are the same as those in Example 1, except that step (S3) is eliminated, that is, the cross-linked precursor I obtained in step (S2) is directly subjected to step (S4).
[0054] Comparative Example 4
[0055] The other conditions are the same as those in Example 1, except that step (S2) is changed to: pre-oxidation precursor, polyacrylic acid (number average molecular weight of about 5000 g / mol) and perylenetetracarboxylic dianhydride are ball-milled in a mass ratio of 100:4:10, with a ball-to-material ratio of 10:1, a rotation speed of 600r, and a ball-milling time of 5h. The obtained mixture after ball milling is sheeted, and the temperature is raised to 600°C at a heating rate of 10°C / min under an argon atmosphere, and kept warm for 5h to obtain a cross-linking precursor I; then step (S4) is performed. That is, steps (S2) and (S3) are combined, and the pre-oxidation precursor and cross-linking agent I and cross-linking agent II are mixed together for cross-linking modification.
[0056] Figure 1 From the constant current charge and discharge curves of the battery after the electrode sheets made of coal tar pitch (XLC), comparative example 1 (OXLC), and example 1 (POXLC) are assembled into batteries, it can be found that compared with the material directly charcoal-burned with asphalt at high temperature, the carbon negative electrode material prepared in example 1 has a higher capacity and the platform capacity is also improved.
[0057] Figure 2 This is a high-resolution projection electron microscopy (HRTEM) image of the hard carbon material obtained in Comparative Example 1 and Example 1. It can be seen that the material after two-step cross-linking modification has curved and closed local graphite domains, and at the same time, it forms a large number of closed-pore structures. This is closely related to the improvement of the capacity of the low-pressure platform area. The formation of closed pores can provide favorable conditions for the precipitation of sodium metal clusters inside the hard carbon, and will not affect the sodium ion diffusion of the negative electrode material. High-temperature calcination reduces the formation of surface oxygen-containing functional groups and defects by the activator, eliminating its effect on the coulombic efficiency of the material. This structure is completely different from the carbon material obtained by direct calcination of asphalt. At the same time, the hard carbon sample of Example 1 obtained by compounding pore-forming agents with a variety of oxygen-containing organic substances is more porous, which will lead to a higher platform capacity.
[0058] Figure 3 From the XRD patterns of the carbon materials of Example 1 (POXLC) and Comparative Example 1 (OXLC), it can be seen that the sodium ion amorphous carbon negative electrode after cross-linking activation has a higher amorphous degree than the carbon material obtained by direct calcination after pre-oxidation, and the modified carbon material has a larger interlayer spacing and lower crystallinity, indicating that the average stacking degree of graphite domains is reduced, and the short-range ordered graphite domains are more conducive to forming a closed microporous structure when cross-linked with each other, thereby accommodating the effective storage of sodium ion clusters in the low-pressure platform area.
[0059] Figure 4The constant current charge and discharge curves of Example 1 (POXLC) at different current densities show that it can still exhibit a high specific capacity at a large current density, indicating that the structure generated by its cross-linking can maintain stability well and maintain a high specific capacity at a large current.
[0060] It can be seen that compared with the asphalt material without cross-linking, the asphalt-based hard carbon material obtained by the two-step cross-linking in Example 1 has a higher specific capacity, and the newly formed pores are conducive to the adsorption and deposition of sodium ions and sodium clusters on its inner surface, and the electrochemical performance is significantly improved.
[0061] Example 2
[0062] The other conditions are the same as those in Example 1, except that in step (S2), polyacrylic acid is replaced by polymethyl methacrylate with a number average molecular weight of 5000, and the mass ratio of the pre-oxidation precursor to polymethyl methacrylate is 100:6.
[0063] Example 3
[0064] The other conditions are the same as those in Example 1, except that in step (S3), perylenetetracarboxylic dianhydride is replaced by terephthalic acid, and the mass ratio of the cross-linking precursor I to terephthalic acid is 100:5.
[0065] Example 4
[0066] The other conditions are the same as those in Example 1, except that in step (S3), perylenetetracarboxylic dianhydride is replaced by 1,3,5-benzenetricarboxylic acid, and the mass ratio of the cross-linking precursor I to 1,3,5-benzenetricarboxylic acid is 100:10.
[0067] Example 5
[0068] The other conditions are the same as those in Example 1, except that step (S3) is changed to: the cross-linking precursor I and perylenetetracarboxylic dianhydride are ball-milled in a mass ratio of 100:10, the ball-to-material ratio is 10:1, the rotation speed is 600r, the ball-milling time is 5h, and the mixture is sheeted after ball milling. After the sheet is sheeted, it is heated to 400°C at a heating rate of 5°C / min under an argon atmosphere, kept warm for 6h, and cooled to obtain the cross-linking precursor II.
[0069] Example 6
[0070] The other conditions were the same as those in Example 1, except that in step (S1), the heating rate was changed from 3°C / min to 10°C / min.
[0071] Application Examples Electrochemical performance test
[0072] The obtained dried negative electrode sheet was assembled into a button cell with a metal sodium negative electrode, a carboxylic acid cellulose separator, and an EC / DEC / 1M NaPF6 electrolyte, and then placed on the Newwell test platform for testing to obtain the first cycle curve shown in Table 1. In the voltage range of 0.001 to 2V, it was first activated at a current density of 20mA / g for 5 cycles, and then charged and discharged.
[0073] The electrochemical properties of the negative electrode materials obtained in the above examples and comparative examples are listed in the following Table 1:
[0074] Table 1 Electrochemical performance data of negative electrode materials
[0075]
[0076]
[0077] From the test results of the half-cells of each embodiment in Table 1, it can be seen that after cross-linking and activating the fossil mineral precursors such as asphalt, the sodium storage capacity and rate performance of the amorphous carbon negative electrode of the sodium ion battery are significantly improved. -1 The first cycle charge capacity at current density is 300mA g -1 Above, 200mA g -1 The first cycle charge capacity at the current density is 230 mAh g -1 The above, while the unmodified comparative example 1 has a specific capacity of 290 mAh / g. It is worth noting that the crosslinking activation conditions need to be properly controlled, and the optimal carbon layer structure and the maximum specific capacity can be obtained by controlling the activation conditions.
[0078] The present invention provides an application of fossil mineral-based pyrolysis amorphous carbon material in sodium ion batteries. The contribution to the prior art is that by using anhydride or carboxylic acid as a cross-linking agent, the cross-linking degree of the precursor is increased, and the characteristics of releasing gas molecules during the pyrolysis process are improved, the porosity inside the carbon material is increased, and the molten state rearrangement of asphaltene is inhibited. When carbonized at high temperature, the local graphite domain can be closed to form a closed hole, which greatly improves the electrochemical performance of the sodium ion battery. It can be understood that in each embodiment of the present invention, although the present invention is described in detail in combination with specific electrolytes, diaphragms, current collectors, active materials, binders, conductive additives, etc., the above is only to meet legal requirements and illustrate the composition of sodium ion batteries, and the present invention is not limited to the given embodiments. Any modification, equivalent substitution and improvement made within the spirit and principles of the present invention using the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a hard carbon material, characterized in that: The following steps are involved: (S1) crushing the asphalt and performing heat treatment in an oxidizing atmosphere to obtain a pre-oxidized precursor; (S2) the pre-oxidized precursor is mixed evenly with the cross-linking agent I, and a cross-linking is performed once under an inert atmosphere and heating conditions to obtain a cross-linked precursor I; the cross-linking agent I is a polymer having a carboxyl group in the side chain; (S3) The cross-linking precursor I and the cross-linking agent II are mixed evenly, and secondary cross-linking is performed under an inert atmosphere and heating conditions to obtain a cross-linking precursor II; the cross-linking agent II is a small molecule aromatic compound containing multiple anhydride and / or carboxyl groups. (S4) The cross-linked precursor II is calcined, cooled and ground under an inert atmosphere to obtain an amorphous sodium ion battery negative electrode material.
2. The preparation method according to claim 1, characterized in that: The asphalt material includes one or more mixtures of coal tar asphalt, petroleum asphalt, natural asphalt and mesophase asphalt; crushed to a particle size of less than 5 mm; and / or The oxidizing atmosphere comprises at least 20% by volume of oxygen, such as oxygen, air, a mixture of nitrogen and oxygen, a mixture of carbon dioxide and oxygen; the oxidizing atmosphere may also contain an atmosphere of ozone; and / or The heat treatment is to slowly heat up to 250-300°C and keep the temperature for 5-10h; preferably, the heating rate of the slow heating is 1-3°C / min.
3. The preparation method according to claim 1, characterized in that: In step (S2), the crosslinking agent I is selected from at least one of polyacrylic acid, polymethacrylic acid and alginic acid; preferably, the number average molecular weight of the crosslinking agent I is 4000-20000 g / mol; more preferably, the amount of the crosslinking agent I is 5-10 wt % of the pre-oxidized precursor.
4. The preparation method according to claim 3, characterized in that: The number average molecular weight of the polyacrylic acid and polymethacrylic acid is 4000-6000 g / mol; the molecular weight of the alginic acid is 10000-20000 g / mol.
5. The preparation method according to claim 1, characterized in that: In step (S2), the process conditions for the primary cross-linking are heat treatment at 300-600°C for 5-10h.
6. The preparation method according to claim 1, characterized in that: In step (S3), the crosslinking agent II is selected from at least one of terephthalic acid, phthalic acid, isophthalic acid, gallic acid, perylenetetracarboxylic dianhydride, trimesic acid, and pyromellitic anhydride.
7. The preparation method according to claim 1, characterized in that: The amount of the crosslinking agent II used is 3-6 wt % of the crosslinking precursor I.
8. The preparation method according to claim 1, characterized in that: In step (S3), the process conditions for secondary cross-linking are firstly heating to 250-400°C at a heating rate of 5-10°C / min, keeping the temperature for 1-2h, and then slowly heating to 400-600°C at a heating rate of 5-10°C / min and keeping the temperature for 3-5h.
9. The preparation method according to claim 1, characterized in that: In step (S4), the hydrocarbon is at least one of methane, ethane, propane, butane, ethylene, acetylene, and toluene; and the calcination is performed by heating the temperature to 1000-1500° C. at a heating rate of 5-10° C. / min and calcining for 3-8 hours.
10. A sodium ion battery hard carbon material, prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Carbonaceous material for non-aqueous electrolyte secondary battery
CN104094458A
Preparation method of sodium ion battery hard carbon material
CN116553512A
Composite negative electrode material, negative electrode plate and sodium ion battery
CN117691074A
Sodium-ion battery negative electrode material based on resin and asphalt as well as preparation method and application of sodium-ion battery negative electrode material
CN117902565A
Method for producing hardly graphitizable carbon material
JP2017103113A
Cited By
Asphalt-based hard carbon material for sodium ion battery and preparation method of asphalt-based hard carbon material
CN120246978A
Asphalt-based hard carbon negative electrode material and preparation method thereof, electrode plate and sodium ion battery
CN122233354A
Composite carbon material, preparation method and application thereof, and alkali metal ion battery
CN122338027A
Sodium-ion battery hard carbon material and preparation method thereof
CN122380342A
